What Are the Alert Fatigue Concerns with Clinical AI? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, with clinical AI applications promising to revolutionize everything from diagn...
Keywords: AI in Clinical Decision Support; Alert; Fatigue; Concerns; Artificial Intelligence; Healthcare; Clinical Decision Support